RECOVERY THROUGH PHYSICAL THERAPY A RADIUS OF FRACTURE ON CHILDREN - Petrariu Ileana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The purpose of this paper is to contribute to the improvement, reducing recovery time for fractures of the radius by applying a specialized and individualized recovery program. The research was conducted within the Physical Therapy and Swimming Complex from Stefan cel Mare University of Suceava. For research we selected a subject with radius fracture who received physicaltherapy treatment during March-May 2016, the 2 times a day, each for 45 minutes.